Incidence of breast cancer in women in the Małopolska Province in 1999-2001 - Rachtan, Jadwiga; Sokołowski, Andrzej; Geleta, Małgorzata; Molong, Łucja (Contemporary Oncology/Współczesna Onkologia, 2004)
The objective of the study was to asses breast cancer risk in women residing in the Małopolska Province taking into account respective counties, in 1999-2001. The source of information were cancer records sent to the Małopolska Cancer Registry. Basing on the available data, average annual number of cases as well as crude and standardized incidence rates per 100 000 were calculated. Differentiation of breast cancer incidence in respective counties of the Małopolska Province is presented in a graphic form as a map prepared using STATISTICA software. In the Małopolska Province in 1999-2001 there was an average number of 980 new cases registered per year. The average percentage of cancer diagnosis confirmed histologically was 80.0%. The most common histological type was the ductal infiltrating carcinoma (78.7% of the total number of cases). The age standardized breast cancer incidence rate in women in Małopolska was 42.8 per 100 000. The highest value of incidence rates were observed in Kraków (60.2 per 100 000), in the Olkusz County (50.1 per 100 000) and in the Wadowice County (49.7 per 100 000), while the lowest rates were observed in the Limanowa (23.3 per 100 000), Nowy Sącz (25.0 per 100 000), and Myślenice (27.6 per 100 000) Counties. In the areas of the highest breast cancer risk in women (Kraków, Olkusz County and Wadowice County) the incidence rate values were on the average 37.4% higher than the general incidence rate in Poland, and 24.0% higher than in Małopolska. The results of studies on breast cancer incidence in respective counties of Małopolska may be helpful in planning cancer care in that area.